Diverse clinical manifestations and prognosis in a couple’s mercury poisoning caused by skin-lightening creams: two case reports and literature review - Ji, Huixia; Chen, Ye; Liu, Dandan; Zhou, Tongzhou; Tang, Yuhua (Frontiers in Medicine, 2025)
Skin exposure to mercury-containing creams occurs most commonly in young and middle-aged women and, in a few cases, in men. This article presents the symptoms and prognosis of a couple who developed mercury poisoning after cosmetic use of similar duration and dosage. Case 1 is a 33-year-old man who developed nephrotic syndrome after using skin-lightening creams containing mercury over 9 months. Renal puncture pathology indicated membranous nephropathy. During the course of the illness, the patient intermittently took Chinese medicine. Approximately 4 months later, the patient developed pulmonary thrombosis and lower extremity venous thrombosis as a result of fatigue driving and had to undergo thrombolysis and filter implantation. A urine mercury level of 65.4 μg/g·creatinine was detected in the patient. The urine protein level remained positive 8 months after mercury removal. Case 2 is a 30-year-old woman, the wife of case 1, who used the same creams for 9 months with her husband and had a urine mercury level of 80 μg/g·creatinine. The patient experienced sleep disturbances, fatigue, and irritability. In Case 2, neurasthenia symptoms were relieved following mercury removal, and no other complications were observed. There have been very few reports regarding male patients developing nephrotic syndrome as a consequence of using cosmetics that contain mercury. However, clinicians should not neglect this cause when dealing with newly diagnosed male patients with nephrotic syndrome. The treatment and prognosis of male patients are less well established, and changes in their condition must be closely monitored.